REVOLUTIONING COMMUNICATION IN NOVEL KEKASIH TERJAUH BY DWITASARI - Widyastuti, Thera (Diksi, 2021)
(Title: Revolutioning Communication in Novel "Kekasih Terjauh" by Dwitasari). The rapid development of technology is running these days. Progress in communication technology make communication between individuals easier and more convenient. The requirement for social interaction causes everyone need communication. Communication and literary works cannot be separated. The way of communication changes with the times. Language as an important element in literature also changes. There is internet which is change our perception about communication. This research will discuss the communication that occurs between the characters in the novel "Kekasih Terjauh" by Dwitasari. The problem in this research is about the revolutioning communication used by the characters in the novel "Kekasih Terjauh". While the purpose of this research is to determine the the revolutioning communication that is taking place in the novel "Kekasih Terjauh". The methodology used is descriptive analysis with literature study as a data collection technique. This research uses theory of character, setting, communication, and also sociology of literature.Keywords: communication, internet, revolution, technology